The Impact of Teaching Aids in Learning of Women's Reproductive Organs For Blind Teenage Students At SLBN A Kota Bandung - Tanbrin, Nita Nitiya Intan; Heryati, Euis; Homdidjah, Oom Sitti; Rahmah, Destiyanti Wahyuni (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
This research explores the impact of puppet media as teaching aids in teaching the anatomy of female reproductive organs to blind children in class 9 at SMPLB N Pajajaran, Bandung. In the context of sexual education for children with special needs, understanding reproductive anatomy is crucial for self-protection against sexual abuse and sexually transmitted diseases. Using a qualitative approach, this study examines strategies, techniques, and methods in inclusive education to help blind children understand female reproductive anatomy. It considers their developmental needs and abilities in selecting suitable learning media. The research aims to benefit students, teachers, and schools by enhancing knowledge and skills related to reproductive health and offering new methods for teaching sexual education. Theoretically, it seeks to advance the development of effective learning tools for blind children. This research is urgent because it promotes awareness and protection of reproductive health among blind students, ensuring inclusive and equitable sexual education. It supports national education goals by addressing the special needs of each child, contributing to a smarter and more inclusive society.